STRATEGIC PATHWAYS AND STRUCTURAL BARRIERS IN UZBEKISTAN’S TRANSITION TO A GREEN ECONOMY - Zokhidov Ulugbek Shokirjon ugli (European Science Publishing, 2025)
Uzbekistan stands at an important turning point on the path to attaining sustainable development among many developing nations. The country set significant goals for the transition to a green economy until 2030 at a time when environmental problems are becoming increasingly relevant throughout the world and the region. This article will critically analyze the strategic directions implemented by Uzbekistan – in particular, measures to develop renewable energy sources, promote green financing and adapt to international environmental obligations. At the same time, the article also covers such factors as systemic problems that hinder progress – outdated infrastructure, institutional restrictions and low environmental awareness of the population.
Keywords: Green economy, environmental obligations, systematic obstacles, strategic directions, Concept Note, energy transition, green finance, sustainable agriculture, green urban development, awareness campaigns, infrastructure gaps, regional comparisons, green sector